The Impacts of Intellectual Capital, Company Size and Company Age on Company's Financial Performance in Indonesia - Pasaribu, Sarmi Nuryusna; Sebayang, Minda Muliana Br (Jurnal Ilmiah Akuntansi Keuangan dan Bisnis (JIKABI), 2023)
This study aims to determine the effect of Intellectual Capital, Company Size and Company Age on Company Financial Performance. The type of research used in this research is quantitative research with a casual associative approach with secondary data types. The population in this study were all food and beverage sub-sector companies listed on the Indonesia Stock Exchange totaling 30 companies using purposive sampling method. Based on the determination of these criteria, there were 14 companies that became the research sample with a total data of 42 observations. The results showed that intellectual capital had a positive and significant effect on the company's financial performance, while company size and company age had no positive and significant effect.